On the Riccati transfer matrix method for repetitive structures - Stephen, N.G. (Mechanics research communications, 2010)
▶ Riccati transform applied to elastostatic analysis of extended repetitive structures. ▶ Eigenvalues of terms within the recursive relationships show why the method is numerically stable. ▶ The process, both backward and forward in space, may be regarded as a numerical analogue of Saint-Venant's principle. The Riccati transfer matrix method is employed in the elastostatic analysis of a repetitive structure subject to various loadings; the eigenvalues of particular terms featuring in the recursive relationships show why the method is numerically stable.